Color Vision Defects among Textile Mill Workers in Lahore: Doi:10.36351/pjo.v36i4.1100 - Omair, Qazi Muhammad; Imtiaz, Hifza; Iqbal, Maryam (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the color vision defects among textile mill workers in Lahore. Study Design: Descriptive cross sectional study. Place and Duration of Study: University of Lahore from June 2019 to December 2019. Methods: Study was done at different textile mills in Lahore, Pakistan. Self-designed proforma was used to record data including age, gender, occupation, any medication or surgery. The workers with best corrected visual acuity of 6/6 and refractive error less than 3.00 D of sphere or astigmatism less than 1 D of cylinder with no history of ocular surgeries were included in the study. Color vision was assessed using Ishihara Isochromatic color plates. Examination of the anterior segment and posterior segment was done by using slit lamp Biomicroscopy and 90 D of condensing lens.Data was entered and analyzed using the SPSS version 22. Results: During this study 1,250 textile mill workers fulfilled the inclusion criteria. Six hundred fifty were males and 600 were females. Only 10 workers were suffering from color vision deficiency, which was 0.8% of the total sample size. All of the color vision deficiency patients were male of different age group. Conclusion: It has been concluded that although textile industry is based on colors, there is no proper color vision examination in our textile sector. Colour vision deficiency awareness should be increased so that everyone in the community is well aware of it. The test of color vision must be made compulsory in pre-employment examination at public and private sector at every Level.